An Analysis of Digital Queuing Systems in Indonesian Banking Services: A Systematic Literature Review - Carrina A. Tesa; M. Syauqi Haris; Wahyu Teja Kusuma (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Queue systems play pivotal roles in banking services, affecting both operational effectiveness and client satisfaction. The issue of long waiting times and unequal distribution of services across all regions of Indonesia remains a significant issue. Using the PRISMA methodology to perform a systematic literature review (SLR), this research investigates the last 5 years of 25 digital queue management academic works. The selection process to narrow this down began with the Sinta and Garuda databases, although more from Scopus were used to validate the research. The research indicates that identified technologies, such as online queue systems, self-service kiosks, and reservation systems, can improve customer satisfaction and experience by greatly decreasing waiting times. However, the majority of the observations are based on theoretical models or narrow case studies, leading to doubts regarding the generalizability of their findings. The effectiveness of the solutions proposed is highly dependent on the region's infrastructure as well as the users' capacity to utilize the available technology. The integration of queue theory and process simulation provides a foundational approach to the design of systems with improved efficiency. However, there are still significant obstacles to overcome: deficient digital infrastructure, low levels of technological literacy, and poorly integrated systems. Sufficient, systematic responses are required to these issues, as well as more localized systematic studies, to improve queue management systems in the context of the Indonesian banking sector.